Corporate communication characteristics of St. Volodymyr university professors in 1834-1884 - Vasylenko, V. (Вісник Черкаського університету. Серія: Історичні науки, 2017)
Introduction. The development of Contemporary Ukrainian history is accompanied by the change of scientific approaches, methodological transformations and prospecting for cutting-edge research tasks. In this respect, the history of higher education is shifting its vector according to the top-down principle, oriented towards everyday life issues. Corporate communication thus plays a significant role in university activity and reflects the specifics of university environment. The Kyiv University foundation aimed to be a centre of russification and polish elite assimilation, which in turn influenced specific interpersonal relationships within the academic community. Purpose. The aim of this paper is to identify separate specific features of corporate communication, introduced by Kyiv University professors on horizontal and vertical levels. Methods. Rejecting ideological impact and involving interdisciplinary perspective into historical studies demand new research strategies and methodology. Historical anthropology enables scholars to reveal the management specificities, the decision-making models and the aspects of communication within the academic society. Results. The paper provides the information on the specific features of corporate relations, having been identified in the process of research, connected to the constant confrontation between the «parties» of professors’ associations in St. Volodymyr University. Originality. This study initially addresses the issue of corporative communication in Kyiv University academic environment. It gives a detailed analysis of horizontal and vertical communication peculiarities of both state and scientific elite. Conclusion. The relationships between professors of St. Volodymyr University were shaped by specific circumstances of institution origin and operation. A substitution of competencies by personal and «party» preferences led to regular conflicts within the academic world and made the sustainable collaboration impossible.